The role of biostimulation in iron bioleaching and purification of quartz sands - Iveta Štyriaková; Igor Štyriak; Katarína Jablonovská (Acta Montanistica Slovaca, 2011)
The biostimulation for iron mineral dissolution and reduction with chelators and organic source were investigated on ferrihydriteand quartz sands contaminated with iron minerals. The finding that bacteria can donate electrons to chelators has importantimplications for the removal of iron impurities from industrial minerals such as quartz sands. The effect of media composition withchelators (EDTA, NTA, AQDS) on the extent of bacterial dissolution of iron mineral was studied under laboratory condition andselected a chelator Na2EDTA was studied under in-situ conditions.A stronger stimulation and continuos Fe dissolution by the form ofEDTA favors its in-situ use. Ultra-fine iron particles coating and impregnating quartz particles are difficult to treat by conventionalmineral processing methods. Biological leaching appears to be the alternative for the effective removal of iron minerals. The in-situremoval of Fe-phases from quartz sands via bioleaching was optimized with regard to the rate of iron reduction and dissolution bybiostimulation with Na2EDTA.